Implementasi Etika Bisnis Islam Pada Aspek Produksi dan Sistem Marketing Bisnis Skincare Ratu Glow - Syaharuddin, Syaharuddin; Irfan, Fitriani; Awaluddin, Awaluddin (Jurnal Iqtisaduna, 2024)
The main problem of this research is how to apply Islamic business ethics in an effort to increase consumer confidence in the Ratu Glow skincare business. This type of research is a qualitative field study, with the research approach used being a normative theological and phenomenological approach. Then the primary data source for this research comes from Ratu Glow management and consumers who have used Ratu Glow skincare. The data collection methods used were observation, interviews and documentation. The results of this research reveal that the Ratu Glow skincare business has implemented Islamic business ethics in its business operations, both in the production aspect and in the marketing aspect. The forms of Islamic business ethics that have been applied to the production aspect of Ratu Glow’s skincare business include the principle of monotheism, the principle of justice, the principle of freedom, the principle of responsibility and the principle of Ihsan. Meanwhile, the business ethics applied to the marketing aspect are honesty, trust, fathana, tabliq and tolerance.